ENHANCING DATA SECURITY IN E- HEALTH CLOUD USING ATTRIBUTE- BASED ENCRYPTION, AES & STEGANOGRAPHY - Trivedi, Adwitiya; Paliwal, Tushar; J, Ramaprabha.; Prabakaran, S. (International Journal of Psychosocial Rehabilitation, 2020)
In recent years, the growth in cloud computing has resulted in its application in multiple fields; one of them is E-Health Cloud. E-Health Cloud is the storage of the patient records in the cloud. The cost of services in health care is skyrocketing and professionals are to find, so the organizations have started adopting IT systems which helps them automate and streamline the process in a very cost-effective method. As the utilization diversifies, the amount of the data stored in the E cloud rapidly increases. Since the type of data in E-Health Cloud is sensitive, the privacy of data becomes a critical concern. This study explores the application of modern encryption techniques (AES and ABE) with steganography to study the storage, sharing and administration of medical data. Further, this paper will be used as a foundation to study techniques such as 3DES to compare with other encryptions and understand the advantages and limitations of each.